Can Company radiation Announcement Influence Investor Sentiment and Predict Abnormal Returns? Tunisia Evidence - Bilel, Hadfi; Khammassi, Ines (Journal of Ecohumanism, 2024)
The purpose of this paper is to observe whether the announcement of company radiation can affect their abnormal return on the Tunisian stock exchange. The sample includes 5 non financial listed stocks in Tunisia Stock Exchange during the years 2012-2021. Company decides to announce its radiation to signal the market that the firm is now processing future prospects, which will result in changing its stock prices. The findings yield qualitatively consistent with the previous research. The result shows that the stock prices move upward significantly after dividend announcements. Abnormal return (AR) and cumulative abnormal return (CAR) from the market model are statistically significantly revealed. Moreover, most event windows show that the stock return becomes lower when the company delisted from stock market. The result is limited to the absence of an important number of firms listed in TSE from this period. Investors in Tunisia react negatively to firms’ radiation and show their preference for dividend to self control, satisfaction and increase their profit. This document provides evidence of the phenomenon of firms’ radiation from markets, we document the impact of delisting announcement on stock returns. Even though the results indicate that Tunisian market react to the announcement of companies’ radiation by managers. Moreover, the timing of delisting decision is affected by some different factor related to the firms’ situation and institutional environment. Tunisian investors react negatively to the announcement to firms delisting from Tunisian market.